Development, characterization and nasal delivery of rosmarinic acid-loaded solid lipid nanoparticles for the effective management of Huntington's disease. (3rd October 2015) - Bhatt, Rahul; Singh, Devendra; Prakash, Atish; Mishra, Neeraj
Abstract: Objective : The objective of the present study was to investigate the potential use of solid lipid nanoparticles (SLNs) as a drug delivery system to enhance the brain-targeting efficiency of rosmarinic acid (RA) following intranasal (i.n.) administration. Materials and methods : The RA-loaded SLNs was prepared by the hot homogenization technique, in which glycerol monostearate (GMS) as lipid, tween 80 and soya lecithin were used as surfactant along with hydrogenated soya phosphatidyl choline (HSPC) as a stabilizer, and were characterized for particle size, zeta potential (ZP), in vitro study. Nasal delivery of the developed formulation followed by the study of behavioral (locomotor, narrow beam, body weight) and biochemical parameters (glutathione, lipid peroxidation, catalase and nitrite) in wistar rat was carried out. Results: Optimized RA-loaded SLNs using tween 80 (SLNPRT) have the mean size of (149.2 ± 3.2 nm), ZP (−38.27 mV) entrapment efficiency (61.9 ± 2.2%). 3-NP-treated rat significantly increased behavioral alterations, oxidative damage as compared with the control group. SLNPRT treatment significantly improved behavioral abnormalities and attenuated the oxidative stress in 3NP-treated rats. However, the nasal delivery of SLNPRT produced significant therapeutic action as compared to intravenous application. In the organ distribution study, brain drug concentration was found to be 5.69 µg, in pharmacokinetic study C max, t max, t 1/2, AUC values were found to be 0.284 µg/ml, 1.5 h, 3.17 h, and 1.505 µg/ml/h, respectively. Conclusion : The encouraging results confirmed the developed optimized RA-loaded SLNs formulation following the non-invasive nose-to-brain drug delivery that is a promising therapeutic approach for the effective management in Huntington disease.